The Teaching of Listening in A Pesantren-based University during Covid-19 Pandemic - Nurrahma Sutisna Putri (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
Abstract This study explores the teaching of listening in pesantren-based university during COVID-19 pandemic. There are 18 male students and 6 female students taking part in the study. They are taking Listening for Daily Conversation course for 7 meetings. The data is collected using questionnaire in the form of Google Form. There were two aspects asked to the respondents; (1)about the materials and (2)about the teaching and learning activity. The study found that; (1)the level of difficulty used by the lecturer teaching Listening for Daily Conversation class needs to be adjusted to students’ current level of competence, (2)lecturer teaching the course at the male campus gave less questions in the assignment compared to lecturer teaching in the female campus who give more questions to the students, (3)male students’ answers are more homogeneous compared to female students’ answers, (4) male students tend to show more happiness and gratefulness compared to female students showed more sadness, (4)almost all of the male students think that them could not meet the lecturers do not affect them. Meanwhile, the female students are more affected, (5)students from both campuses  needed assistance from the Internet, books, dictionary, and their friends, (6)lecturers from both campuses provided assistance to the students. Being an effective English lecturer requires being able to help and assist students in their learning process, (7) can be interpreted that students’ suggestions on what needs to be improved are divided into the teaching and learning activity for male students and students themselves for female students.  It is hoped that this study will contribute to the body of knowledge in terms of the teaching of listening during COVID-19 pandemic.